Efisiensi Bahan Bakar Pada Mesin Chooper - Wiyogo Wiyogo; Yesninopy; Maria Ulfah; Desvarado Sinamulang; Trio Al Khafi (FKIP Universitas Palangka Raya, 2023)
Increasing fuel consumption efficiency is a challenge in the development of choppers machine. Multiple testing procedures must be performed in order to improve. aims to evaluate the performance of automobiles running on fuel that meets RON 90 and 92 requirements. The test is performed three times with a consistent angle of cut of 10 degrees at an engine speed of 2,700 rpm.The duration of the combustion engine's operation has an impact on fuel usage. The average consumption difference between the 1800 and 1200 second tests utilizing the cutting load at RON 90 is up to 2% better. With the same amount of time as the prior test, the RON 92 testing showed a 0.5% improvement in fuel efficiency. Speed increases result in more thorough combustion, thus reduces fuel usage. High chopping speeds can be used by users to improve fuel economy.